Graves’ ophthalmopathy: the clinical and psychosocial outcomes of different medical interventions – a systematic review - Maralyn Druce; Ejaz Ansari; Oyinlola Maria Bello (BMJ Open Ophthalmology)
Background Graves’ ophthalmopathy is a complex autoimmune disorder that can significantly affect quality of life (QoL), vision and physical appearance. Recently, a deeper understanding of the underlying pathogenesis has led to the development of novel treatment options.Aims The purpose of this review is to explore the current literature on conventional and novel treatment modalities and to evaluate which interventions provide the most favourable psychological and clinical outcomes in patients with moderate to severe, active Grave’s ophthalmopathy. For example, QoL is an important psychosocial outcome of disease management. However, available literature demonstrates that not all clinically effective treatment options improve patients’ QoL.Methods A systematic literature review was conducted to assess the clinical and psychosocial outcomes of different therapies for Graves’ ophthalmopathy. An extensive database search of Ovid Medline, Ovid Embase and Cochrane Central Register of Controlled Trials was conducted. Studies generated were reviewed and the relevant selected data were retrieved and analysed.Results Results showed intravenous steroids, rituximab (RTX), tocilizumab and teprotumumab were all significantly effective in improving Clinical Activity Scores. Orbital radiotherapy showed a slight improvement in proptosis and diplopia. All interventions were safe with few serious adverse events being reported across all studies. All treatment modalities demonstrated beneficial improvements in both components of the Graves’ Ophthalmopathy-QoL (QoL) questionnaire, apart from orbital radiotherapy which only demonstrated improvements in the visual functioning subscale. Teprotumumab was identified to be the most effective intervention for improving both clinical and psychosocial outcomes. However, further research needs to be conducted to evaluate its side effect profile and cost-effectiveness. Nonetheless, with time it has the potential to be a first-line treatment option in the management of active moderate to severe Graves’ ophthalmopathy.